1993
DOI: 10.1021/bi00090a020
|View full text |Cite
|
Sign up to set email alerts
|

Binding of acylated peptides and fatty acids to phospholipid vesicles: Pertinence to myristoylated proteins

Abstract: We studied the binding of fatty acids and acylated peptides to phospholipid vesicles by making electrophoretic mobility and equilibrium dialysis measurements. The binding energies of the anionic form of the fatty acids and the corresponding acylated glycines were identical; the energies increased by 0.8 kcal/mol per number of carbons in the acyl chain (Ncarbon = 10, 12, 14, 16), a value identical to that for the classical entropy-driven hydrophobic effect discussed by Tanford [The Hydrophobic Effect (1980) Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
432
2
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 519 publications
(476 citation statements)
references
References 63 publications
40
432
2
2
Order By: Relevance
“…A protein standard curve is generated in parallel for each protein in order to determine what percentage of total added protein has pelleted with the vesicles. Molar partition coefficients (K), as defined by Peitzsch and McLaughlin [45] We have used this method extensively for studying binding of PH and FYVE domains to vesicles of different lipid compositions [20,46]. In these cases, the K D estimates agree very well with results obtained for binding to equivalent vesicles from ITC (for PLC 1 ) and surface plasmon resonance studies (see Section 2.3.3.5).…”
Section: Vesicle-binding Assaymentioning
confidence: 53%
“…A protein standard curve is generated in parallel for each protein in order to determine what percentage of total added protein has pelleted with the vesicles. Molar partition coefficients (K), as defined by Peitzsch and McLaughlin [45] We have used this method extensively for studying binding of PH and FYVE domains to vesicles of different lipid compositions [20,46]. In these cases, the K D estimates agree very well with results obtained for binding to equivalent vesicles from ITC (for PLC 1 ) and surface plasmon resonance studies (see Section 2.3.3.5).…”
Section: Vesicle-binding Assaymentioning
confidence: 53%
“…We use a molar partition coefficient K (49,50) to describe the binding of the peptide to lipid vesicles without making assumptions about the absorption mechanism. The molar partition coefficient K is defined by the equation …”
Section: Materials-1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholinementioning
confidence: 99%
“…In a series of biophysical investigations of the thermodynamics of insertion of lipid-modified model peptides in vesicles, functioning as model membranes, the contribution of the lipids to lipopeptide membrane affinity was determined. [45][46][47] This showed that an Nmyristoyl or an S-farnesyl group alone cannot contribute enough hydrophobic character to maintain stable membrane insertion of peptides, and therefore also of proteins.…”
Section: Methodsmentioning
confidence: 99%